Efectos del aluminio sobre el crecimiento de genotipos de maíz (Zea Mays L.) tolerantes y susceptibles (1992)
In the Graduate School of Chapingo, Mexico, experiments were conducted both, in nutrient solutions and in an acid soit to determine the effects of Aluminum (Al) on growth of two corn (Zea mays L.) genotipes tolerant (Cr10110) and susceptible (ICA V-109). Three Al concentrations were used 0.0, 0.15 and 0.225 mM in nutrient solution, to 6.2 ± 0.2 pH in the control plant (0.0 mM Al) and 4.2 + 0.1 for the other tratments. The Ienght, the dry-weight of the root and the aerial part disminushed progressively as the Al concentration increased. The roots of the susceptible genotipe were atrophied, thickened and became brittle. Most of the Al acumulated in the root but in a greater proportion in the tolerant genotipe. The P, Ca, Mg and Fe concentration in the roots decreased with Al addition to the solution. Three levels of Al saturation were tested in the soil (0,38 y 450/6). The effects were similar but less intensive than those observed in the nutrient soution. Through Chemical analysis of the soil saturation extract and the nutrient solution, and the utilization of Geochem computer program was found that the ionic form of Al predominant was Al. In the nutrient solution this form represented 78% of total Al but in the soil solution it was 45% only; due to these differences in free Al concentration between the nutrient solution an the soil, the titotoxic effects of Al in soil were less drastic.